The Relationship Between Family Function and Adolescent Autonomy in The Rural and Urban Area - Mulyati Mulyati; Kenty Martiastuti (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2018)
This study aims to analyze the function of families in urban and rural areas as well as its relationship with adolescent autonomy by using cross sectional study method. The data collection time was conducted in September 2016. By proportional random sampling method, there were 72samples at SMPN 2 Bogor (representing urban area) and 72 people at SMPN 2 Parung (representing rural area). Research data includes family characteristics, family functions divided into 3 dimensions (10 sub-scales) and adolescent autonomy consisting of 3 dimensions (value, emotional and behavioral). To see the correlation, the Pearson Correlation test was used and to seedifferences in family function characteristics and gender-based autonomy was seen by the Independent T-test differential test. The results showed that the average score of family function in urban areas was 118.44, while in rural areas 121.12. This shows the function of families in ruralareas better than in urban areas. The average score of urban adolescent autonomy is 81.21, while in rural areas it is 77.29. This difference is significant at 99% confidence level. Adolescent autonomy is positively correlated with family function of personal growth dimension with correlation coefficient of 0.207 (at 95% confidence level). This shows that the better familyfunction then the better the adolescent autonomy.